UPAYA MENINGKATKAN PROSES PEMBELAJARAN DAN HASIL BELAJAR IPA MELALUI PENDEKATAN KETERAMPILAN PROSES - Ratna Windhasari; Widodo Budhi (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The purpose of this research was describe about process skills approach used to improve learning process and science achievement students of class VI SDN Giricahyo, Gunungkidul. This research used Classroom Action Research and implemented in two cycle. Data collection techniques using observation, testing, and documentation. Learning process result 67,09% in cycle I, increased 80,10% in second. The precentage of learning outcomes in precycle was 35,71%, increased 64,29% in first cycle and increased 78,57% in the second. So, it can be included that process skill approach can improve learning process and science achievement.Â